2014
DOI: 10.1007/s00438-014-0952-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 4438 novel lincRNAs involved in mouse pre-implantation embryonic development

Abstract: Long intergenic non-coding RNAs (lincRNAs) as a key group of non-coding RNAs have gained substantial attention. Though lincRNAs have been systematically explored in various mouse tissues and cell lines, large-scale identification of lincRNAs in mouse pre-implantation embryonic development (PED) process has not be documented previously. Therefore, it is important to identify and characterize novel lincRNAs that may be involved in PED. In this paper, we performed transcriptome assembly based on published single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 76 publications
2
20
0
Order By: Relevance
“…Considering the incomplete annotation in pig, herein we performed genome-wide characterization of novel lincRNAs using two signature tools independent of known annotations. As results, our newly identified lincRNAs in pig shared many characteristics with those in other mammalian species31617272829. They are lower in exon number, longer in exon, shorter in whole transcripts, lower in expression level and more specific in expression patterns than protein coding transcripts.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Considering the incomplete annotation in pig, herein we performed genome-wide characterization of novel lincRNAs using two signature tools independent of known annotations. As results, our newly identified lincRNAs in pig shared many characteristics with those in other mammalian species31617272829. They are lower in exon number, longer in exon, shorter in whole transcripts, lower in expression level and more specific in expression patterns than protein coding transcripts.…”
Section: Discussionsupporting
confidence: 54%
“…To quantitatively assess the expression specificity of each transcript, we applied an entropy-based metric that relies on Jensen-Shannon distance-based algorithm to calculate expression specificity score of each transcript27. Consistent with our previous observation31617, we have also found that our predicted pig lincRNAs show higher JS scores on average than protein-coding genes (mean 0.83 and 0.76; Kolomogorv-Smirnov Test, P -value < 2.2 × 10 −16 ) (Fig. 3B).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The identification and characterization of goat lncRNAs, particularly in fetal skeletal muscle development, have been very limited compared with lncRNAs in human [2, 48] and other model organisms [3, 49]. In goat skeletal muscle, the main focus has been on genes and miRNAs rather than on lncRNAs [44, 45, 50, 51].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, ncRNAs shorter than 200 nucleotides are usually described as small/short ncRNA, such as microRNAs (miRNAs), PIWI-interacting RNAs (piRNAs), small interfering RNAs (siRNAs), and classical ncRNAs such as ribosomal RNAs (rRNAs), transfer RNAs (tRNAs), and small nucleolar RNAs (snoRNAs), whereas ncRNAs longer than 200 nucleotides are described as long ncRNAs (lncRNAs). In the past few years, an increasing number of lncRNAs have been discovered in mammal, including Homo sapiens [1, 2], Mus musculus [37], Bos taurus [8, 9], Sus scrofa [1013], and Ovis aries [14]. And accordingly unveiled that lncRNAs play critical roles in biological processes like transcriptional regulation [1517], epigenetic modification [1820], development [2123], cell differentiation [2426], as well as in some diseases [2729].…”
Section: Introductionmentioning
confidence: 99%